PENGARUH LAMA APLIKASI DAN JENIS BAHAN PENCAMPUR SERBUK KALSIUM HIDROKSIDA TERHADAP KEKERASAN MIKRO DENTIN SALURAN AKAR - Andina Rizkia Putri Kusuma (Odonto : Dental Journal, 2016)
Background: Calcium hydroxide (Ca(0H)2) has a beneficial biological properties as intracanal medicament. However, the direct contact of Ca(OH)2 with the root canal dentine can affect the physical properties and increasing the root fracture risk of treated tooth. This study aimed to determine the effect of application periods Ca(OH)2 mix with glycerin and chlorhexidine digluconate 2% on the micro hardness of root canal dentine.Method: Thirty extracted mandibular first premolars were use in this study. The crowns of the teeth were removed and the canals were prepared with crown- down technique. Each root was sectioned transversely on cervical third of 5 mm thickness and then they were mounted on acrylic resin. The specimens were randomly divided into 6 groups of 5 root segments each. In group IA, IB and IC Ca(0H)2 — glycerin mix were applicated during in a row two weeks contact, four weeks contact and twelve weeks contact. Whereas in group IIA, IIB and IIC Ca(0H)2 - chlorhexidine digluconate 2% mix were applicated during in a row two weeks contact, four weeks contact and twelve weeks contact. During the treatment period, the subjects were kept in an incubator at 37 ° C. Vickers Indenter Microhardness Tester was used to measure the micro hardness of root canal dentine after direct contact with Ca(OH)2 paste.Result: The results showed that the contact periods were effected on dentin micro hardness, while the type of vehicle was not significant.Conclusion: Greatest dentin micro hardness value shown on the application Ca(OH)2 – glycerine paste during two weeks, while the smallest value shown on the application pasta Ca(OH)2 -glycerine during twelve weeks.